2018
DOI: 10.1177/1756286418770626
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of experimental and human stroke with agents approved for multiple sclerosis: a systematic review

Abstract: Background:‘Thromboinflammation’ describes a novel concept in stroke pathophysiology that has opened up the possibility of immunotherapeutic approaches which could become promising strategies for targeted stroke therapies in the future.Methods:We reviewed current evidence for agents approved for multiple sclerosis in preclinical and clinical stroke studies. A systematic review was performed in accordance with the PRISMA statement, searching MEDLINE, the Cochrane Central Register of Controlled Trials, and refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…166 Small clinical trials have shown that fingolimod is well tolerated; however, due to small patient numbers and heterogeneity of the trials, no definitive answer on the efficacy of this therapy can be made at this time. 167 Subcutaneous interleukin-1 receptor antagonist (Anakinra) is another immunomodulatory therapy currently being trialled as an adjunct to thrombolysis in ischemic stroke. 168 This intervention is backed up by many years of animal model evidence, systematic review and meta-analysis 169 and a multicentre randomised pre-clinical trial confirming its efficacy in improving stroke outcome.…”
Section: Multi-target Versus Mono-target Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…166 Small clinical trials have shown that fingolimod is well tolerated; however, due to small patient numbers and heterogeneity of the trials, no definitive answer on the efficacy of this therapy can be made at this time. 167 Subcutaneous interleukin-1 receptor antagonist (Anakinra) is another immunomodulatory therapy currently being trialled as an adjunct to thrombolysis in ischemic stroke. 168 This intervention is backed up by many years of animal model evidence, systematic review and meta-analysis 169 and a multicentre randomised pre-clinical trial confirming its efficacy in improving stroke outcome.…”
Section: Multi-target Versus Mono-target Therapiesmentioning
confidence: 99%
“…166 Small clinical trials have shown that fingolimod is well tolerated; however, due to small patient numbers and heterogeneity of the trials, no definitive answer on the efficacy of this therapy can be made at this time. 167…”
Section: Multi-target Versus Mono-target Therapiesmentioning
confidence: 99%
“…The timing of outcome assessment is another factor that contributes to contradictory results between mouse and human studies. While in most clinical studies the neurological outcome is measured in patients up to several months after the stroke (usually 90 days), a vast majority of preclinical studies in mice focus only on the first days after the stroke ( Veltkamp and Gill, 2016 , Dreikorn et al, 2018 ).…”
Section: Experimental Basis For the Clinical Trials On Immunomodulatomentioning
confidence: 99%
“…Until 2015, seven animal studies exploring the effects of natalizumab on IS had been published [17]. The majority of them reported a reduction in infarct size with natalizumab administration [32][33][34][35] and an improvement in recovery outcomes [34,35].…”
Section: Dmds With Clinical Evidencementioning
confidence: 99%
“…Given the attention inflammation and immune activation has been gathering in the context of IS [14], and the fact that MS treatment modalities targeting the CNS are usually immunosuppressive/immunomodulatory [15,16], research is being conducted on whether substances used in MS can ameliorate IS parameters and recovery. In fact, studies in the respective experimental models have shown that treatment modalities fitted to MS may indeed be beneficial in IS [11,17].…”
Section: Introductionmentioning
confidence: 99%